2016
DOI: 10.1097/iae.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Macular Buckling Using a Three-Armed Silicone Capsule for Foveoschisis Associated With High Myopia

Abstract: Macular buckling with a three-armed adjustable silicone capsule resulted in anatomic and visual improvement in eyes with myopic foveoschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Parolini et al (2015) found that combined vitrectomy and buckling took more surgical time and led to more complications and therefore suggested that macular buckling alone should be the first choice for MTM. Our previous study using a three-armed adjustable silicon capsule in highly myopic eyes with foveoschisis and found that none of the eight patients enrolled in the study required secondary surgery during the follow-up time of about 1 year (Liu et al 2016). In the present study, the need for a second surgery in the buckling group was only one of the 40 enrolled patients (2.5%).…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Parolini et al (2015) found that combined vitrectomy and buckling took more surgical time and led to more complications and therefore suggested that macular buckling alone should be the first choice for MTM. Our previous study using a three-armed adjustable silicon capsule in highly myopic eyes with foveoschisis and found that none of the eight patients enrolled in the study required secondary surgery during the follow-up time of about 1 year (Liu et al 2016). In the present study, the need for a second surgery in the buckling group was only one of the 40 enrolled patients (2.5%).…”
Section: Discussioncontrasting
confidence: 40%
“…A retrospective trial demonstrated that there was limited BCVA improvement in the vitrectomy group but that there was significantly increased BCVA in the macular buckling group in highly myopic eyes with retinal detachment and FTMH (Ripandelli et al 2001). Our previous study found that macular buckling significantly improved the BCVA followed for about 1 year (Liu et al 2016). In the present study, in the buckling group, the BCVA improved by about 21 letters; in the vitrectomy group, the mean improvement of BCVA was about four letters, partially because there were more patients in which MD and FTMH occurred and more patients who developed mild to severe cataracts, which cause worsened BCVA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…19,20 The use of a scleral buckle to reduce the tractions secondary to staphyloma has been reported with good anatomical and functional results. [21][22][23][24] Recent studies have shown that macular buckles are safe and well tolerated, even after long-term follow-up, and have a very low rate of complications. Therefore, the authors suggested that macular buckles should be used alone as the first intervention, whereas vitrectomy should be used in combination with a macular buckle or as a second-line approach in MTM eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The buckling exoplant was prepared under sterile conditions at the time of surgery using a silicone sponge, silicone band and titanium plate at the time of surgery, which was previously reported (Liu et al. ). The silicone sponge was tunnelled using a 19‐gauge needle, and the titanium plate was then inserted into the tunnel.…”
Section: Methodsmentioning
confidence: 99%